Pertanggungjawaban Pidana Pelaku Tindak Pidana Pengancaman dengan Revenge Porn dalam Era Digital di Kota Bandar Lampung - Abdullah Husein Al Aziz; Zainudin Hasan (Pusat Riset dan Inovasi Nasional, 2025)
In the digital era, the development of information technology has a significant impact on various aspects of life, including sexual crimes. One form of crime that is increasingly rampant is revenge porn, where the perpetrator spreads intimate content without the victim's consent as a form of threat. This study aims to analyze the criminal liability of perpetrators of criminal acts of threats through revenge porn and the challenges faced in law enforcement. The research method used is a normative legal study with a qualitative approach. The results of the study show that although there are laws regulating the protection of personal data and sexual crimes, there are still many obstacles in implementing the law, including minimal public awareness and lack of strong evidence. This study recommends the need to increase legal education for the public and strengthen regulations to protect victims and take firm action against perpetrators. Thus, it is hoped that a safer and more responsible digital environment can be created.